Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2025)
Table of Content: 1. Analysis of Key Social and Economic Factors of Farmers Benefiting from Grants Provided by the Rural Economic Growth and Employment Project within Savings and Credit Groups in Jordan Dr. Amin Osama Shammout ,Eng. Zaid Fahed Al-Nsour ,Eng. Mohammad Abd Al-Fattah Abo Hammour 2. Review Paper on the Impact of Climate Change (Temperature, Winds, and Rainfall) on Archaeological Sites in Libya and Mediterranean Basin Countries in Recent Decades Ms. Aya N. Ashuraks, Ms. Zuhur S. Lahrsh ,Ms. Retaj F. Altarhony, Dr. Elhadi E. Abugrean, Co-Prof. Yosof M. Khalifa 3. Compensatory growth in female Nubian goats in Sudaneffect on carcass characteristics, external body measurements and non carcass components (B) Co-Prof. Yagoub Magboul Yagoub ,Prof. Salih Ahmed Babiker 4. The level of application by cow breeders of scientific recommendations related to hemorrhagic fever disease in the Gogjali region Mohammed Ahmed Mahal